Recent updates on anticancer mechanisms of polyphenols - Sharma, Eshita; Attri, Dharam Chand; Sati, Priyanka; Dhyani, Praveen; Szopa, Agnieszka; Sharifi-Rad, Javad; Hano, Christophe; Calina, Daniela; Cho, William C. (Frontiers in Cell and Developmental Biology, 2022)
In today's scenario, when cancer cases rapidly increase both in developed and developing countries, anti-cancerous plant-based compounds become imperative. Numerous plants have been used in folk medicine against numerous diseases worldwide due to their polyphenols. Given the evolving necessity of exploration and understanding of mechanisms of polyphenols for the treatment of cancer, this review is about different anti-cancer polyphenols viz., (i) Quercetin, (ii) Epigallocatechin, (iii) Curcumin, (iv) Silibin, (v) Apigenin, (vi) Luteolin, (vii) Genistein, (viii) Protocatechuic acid, (ix) chlorogenic acid and (x) eupatorine within several realms of existing knowledge on molecules mentioned above such as the mechanism of action and different promising scientific studies on their antitumor effect. Studies on the molecular mechanisms of action of polyphenols published in specialized databases such as Web of Science, Pubmed/ Medline, Google Scholar, Science Direct were used as sources of information. The plant-based polyphenols offer an established efficacy against chemically and induced tumor growth, with lesser side effects. They have the ability to sensitize cells to different therapies and boost biotherapy efficacy. Further experimental pharmacological studies are still needed to evaluate their in vivo efficacy, possible side effects and toxicity. Clinical trials are also needed to establish effective doses in humans. The polyphenols can be used to design a comprehensive treatment in conjugation with existing cancer drug regimens and treatments like chemotherapy and radiotherapy.